2013
DOI: 10.1080/01630563.2013.819515
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Stability Estimates for Ill-Posed PDE Problems by Using Interpolation

Abstract: Abstract. The focus of this paper is on conditional stability estimates for illposed inverse problems in partial differential equations. Conditional stability estimates have been obtained in the literature by a couple different methods. In this paper we propose a method called interpolation method, which is based on interpolation in variable Hilbert scales. We are going to work out the theoretical background of this method and show that optimal conditional stability estimates are obtained. The capability of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 77 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…In [42], under the assumption of the a-priori bound condition (14), the authors established the following condition stability by using the interpolation method:…”
Section: Conditional Stability and Regularization Methods 21 Conditiomentioning
confidence: 99%
“…In [42], under the assumption of the a-priori bound condition (14), the authors established the following condition stability by using the interpolation method:…”
Section: Conditional Stability and Regularization Methods 21 Conditiomentioning
confidence: 99%
“…subsequently, using the result of conditional stability in (15), there holds that Ultimately, we can prove the result of convergence (47) by combing (A20) with (A24).…”
Section: Proof Of Lemma 2 By Settingmentioning
confidence: 95%
“…It can be found that many scholars have researched this kind of problem in the aspect of theory and algorithm, such as [5][6][7][8][9][10][11][12][13][14][15][16][17], and so on. In [14], the author solved (4), (5) by constructing a generalized Tikhonov regularization method, meanwhile derived the a-priori convergence estimate of regularized method.…”
Section: Introductionmentioning
confidence: 99%
“…A famous theorem by A. N. Tikhonov, see [11], asserts that the problem is conditionally well-posed whenever the set M ⊂ X is compact. For some further discussion and examples concerning conditional well-posedness we also refer to [4,5,14]. Proof.…”
Section: Modulus Functionsmentioning
confidence: 99%
“…Tight bounds for the modulus of continuity ω Mϕ can be obtained under additional geometric (convexity) assumptions by means of general interpolation results within the framework of variable Hilbert scales, and we mention [13] for an early work on this. More recently this is pursued within the framework of conditionally stability estimates, see the recent study [14].…”
Section: Smoothness Classes In Hilbert Spacementioning
confidence: 99%